Integrasi Media Interaktif Wordwall dan Slido dalam Pembelajaran Landeskunde di Tingkat Sekolah Menengah Atas - Sobara, Iwa; Indriwardhani, Sri Prameswari; Sulistio, Bambang (Nexus Publishing, 2025)
This community service activity aimed to enhance the capacity of German language teachers in Central Java in teaching Landeskunde (cultural, geographical, and social knowledge of German-speaking countries) through the integration of interactive media Wordwall and Slido. The activity was carried out on July 18, 2025, at SMAN 3 Surakarta, in collaboration with the Indonesian Association of German Language Teachers (IGBJI) Central Java Branch, and was attended by 30 teachers from various secondary schools. The implementation methods included training on media usage, practice mentoring, and data collection through questionnaires. The results showed that most teachers were already familiar with Wordwall, but its use for Landeskunde materials was still limited. Meanwhile, Slido had not been widely used. The main challenges in teaching Landeskunde included limited time, teaching resources, and engaging methods. However, the majority of teachers expressed their willingness to use Wordwall and Slido if adequate guidance and training were available. This activity made a tangible contribution by broadening teachers’ perspectives on the use of digital media for more interactive and contextual cultural learning.